(untitled) (Analysis in Theory and Applications, 2018)
An elementary, but very useful tool for proving inequalities for polynomials with restricted zeros is the Bernstein or Lorentz representation of polynomials. In the present paper, we give two classes of Lorentz polynomials, for which the Erd00f6s-type inequality holds.